Paper-Based Analytical Device For Detection of Metal, Non-Metal, and Organic Pollutants: Review - Rieda Nurwulan Septyani; Aliya Nur Hasanah (Farmaka, 2018)
AbstractThe environment is the unity of space with all things, energy, circumstances, and living things, including human and his behavior, which affects nature itself, continuity of life, and human welfare and other living beings. Today, the environment has been polluted by the impact of intentional and unintentional human activities. To detect that an environment is contaminated the method it still expensive and difficult, that's why the method to analysis environmental pollution is still rarely done. Paper-based Analytical Device is an analytical method that is now often used to detect many things, from chemical compounds, bacteria, pollutants, and use for diagnostics. In this method, only samples with small volumes are required. Nor does it need external support equipment because the sample fluids are controlled largely by capillarity and evaporation. Many researchers now use PAD as an alternative method to test the contaminants present in an environment such as metal contaminants, non-metals, and organic compounds.Keywords: Environmental pollution, Paper-based Analytical Device, metal, non-metal, organic compound.